2022
DOI: 10.3390/d14020065
|View full text |Cite
|
Sign up to set email alerts
|

Improved Chironomid Barcode Database Enhances Identification of Water Mite Dietary Content

Abstract: Chironomids are one of the most biodiverse and abundant members of freshwater ecosystems. They are a food source for many organisms, including fish and water mites. The accurate identification of chironomids is essential for many applications in ecological research, including determining which chironomid species are present in the diets of diverse predators. Larval and adult chironomids from diverse habitats, including lakes, rivers, inland gardens, coastal vegetation, and nearshore habitats of the Great Lakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous studies reported that chironomid larvae (characterized by red color and filament shape) are one of the best prey for water mites (Vasquez et al 2022). Ory et al (2017) and Wicaksono et al (2021b) confirmed that aquatic biota may feed on MPs that are like their prey in color and shape.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies reported that chironomid larvae (characterized by red color and filament shape) are one of the best prey for water mites (Vasquez et al 2022). Ory et al (2017) and Wicaksono et al (2021b) confirmed that aquatic biota may feed on MPs that are like their prey in color and shape.…”
Section: Discussionmentioning
confidence: 64%
“…Research related to conservation and environmental monitoring generates better insights when using taxonomic resolution at the genus or species levels (Lenat & Resh, 2001). Furthermore, for some groups such as Chironomidae, a more accurate taxonomic resolution is indicated for many applications in ecological research (Vasquez et al, 2022), to indicate phylogenetic structure (Baranov et al, 2021), and for the status Acta Limnologica Brasiliensia, 2022, vol. 34, e10…”
Section: Discussionmentioning
confidence: 99%
“…The chironomid COI barcode approach (Kang et al, 2022, Vasquez et al, 2022 is widely and effectively used to characterize chironomids at the species level. Cytochrome C Oxidase Subunit I (COI) gene was amplified following established protocols using the pairs of primers, LCO1490: 5'-GGTCAACAAATCATAAAGATATTGG-3' and HCO2198: 5'-TAAACTTCAGGGTGACCAAAAAATCA-3' as described by Kim et al (2012); and TL2-N-3014 (Pat): 5'-TTCAATGCACTTATTCTGCCATATTA-3') and C1-J-2138 (Jerry):…”
Section: Amplification Of Cytochrome C Oxidase Subunit I Genementioning
confidence: 99%